Current status, breeding strategies and future prospects for managing chilli leaf curl virus disease and associated begomoviruses in Chilli (Capsicum spp.) - Nalla, Manoj Kumar; Schafleitner, Roland; Pappu, Hanu R.; Barchenger, Derek W. (Frontiers in Plant Science, 2023)
Chilli leaf curl virus disease caused by begomoviruses, has emerged as a major threat to global chilli production, causing severe yield losses and economic harm. Begomoviruses are a highly successful and emerging group of plant viruses that are primarily transmitted by whiteflies belonging to the Bemisia tabaci complex. The most effective method for mitigating chilli leaf curl virus disease losses is breeding for host resistance to Begomovirus. This review highlights the current situation of chilli leaf curl virus disease and associated begomoviruses in chilli production, stressing the significant issues that breeders and growers confront. In addition, the various breeding methods used to generate begomovirus resistant chilli cultivars, and also the complicated connections between the host plant, vector and the virus are discussed. This review highlights the importance of resistance breeding, emphasising the importance of multidisciplinary approaches that combine the best of traditional breeding with cutting-edge genomic technologies. subsequently, the article highlights the challenges that must be overcome in order to effectively deploy begomovirus resistant chilli varieties across diverse agroecological zones and farming systems, as well as understanding the pathogen thus providing the opportunities for improving the sustainability and profitability of chilli production.